Implementasi Program Pengajaran Sekolah Minggu di Gereja Baptis Kasih Karunia Simalingkar sebagai Bentuk Pengabdian Masyarakat - Gracela Gracela; Elmina Elmina; Elfrida Elfrida; Gressa Gressa; Josua Josua (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research explores the role of Sunday school teachers in the growth and development of children at Kasih Karunia Baptist Church Simalingkar. Sunday school teachers play an important role in shaping children's character through spiritual and moral education. Creativity in teaching is the key to delivering material in a way that is interesting and relevant to children. Community service by Sunday school teachers involves children in activities that strengthen social and moral values, such as social service projects. The implementation of the Sunday School Teaching (PSM) program at this church, which is supported by IAKN Tarutung students, aims to increase religious and moral understanding, discipline, responsibility, as well as children's talents and creativity. This program also makes a positive contribution to the surrounding community. The research uses qualitative descriptive methods through interviews, observation and documentation analysis. Results showed significant improvements in children's religious understanding, discipline, responsibility and creativity, as well as a positive impact on the community. These findings emphasize the important role of creative Sunday school teachers in shaping children's character and strengthening social ties in the community.